Pengaruh Implementasi Akuntansi Hijau terhadap Kinerja Keuangan dan Keberlanjutan Perusahaan di Sektor Manufaktur di Indonesia - Nasrul Kahfi Lubis; Nurliza Lubis (Worksheet : Jurnal Akuntansi, 2026)
This study aims to analyze the impact of green accounting implementation on financial performance and sustainability of manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2023 period. In this research, green accounting is measured based on environmental disclosure scores in sustainability reports, while financial performance is measured using Return on Assets (ROA) and Net Profit Margin (NPM), and corporate sustainability is measured based on sustainability disclosure scores following the Global Reporting Initiative (GRI) standards. The data used consists of financial reports and sustainability reports from 50 manufacturing companies, totaling 250 observational data points analyzed using multiple linear regression. The results indicate that the implementation of green accounting has a significant positive impact on both financial performance and corporate sustainability. Additionally, financial performance also positively influences corporate sustainability. This study provides evidence that the application of green accounting not only supports the achievement of sustainability goals but also enhances a company's financial performance, contributing to its long-term competitiveness in the market.